Alzheimer's Disease: Explore beta-amyloid, tau proteins, and neuroinflammatory markers like TNF-α as indicators of Alzheimer's progression - Abbood, Sharara Fadhil; Alnasrawi, Taha H; Mashlool, Zahraa Talib (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects millions globally, leading to cognitive decline and, ultimately, death. Key pathogenic hallmarks of AD include the accumulation of beta-amyloid plaques and tau protein tangles in the brain, accompanied by neuroinflammatory responses. The aim of this study is to analyze the serum levels of neuroinflammatory markers, particularly TNF-α, along with beta-amyloid and tau proteins, to better understand their roles in Alzheimer's progression. A cohort of 100 AD patients, aged 60 to 85, was compared with a control group of 50 healthy individuals of similar age. Levels of TNF-α, beta-amyloid, and tau proteins were measured using an enzyme-linked immunosorbent assay (ELISA). Findings revealed significantly higher levels of TNF-α, beta-amyloid, and tau in the AD group compared to the control group, suggesting a correlation between inflammatory processes and protein aggregation in the progression of Alzheimer's. This study highlights the potential of these biomarkers as diagnostic tools for early detection and as targets for therapeutic intervention to slow cognitive decline in AD patients.